Circulating Fatty Acids and Risk of Coronary Heart Disease and Stroke: Individual Participant Data Meta‐Analysis in Up to 16 126 Participants. Issue 5 (3rd March 2020) - Borges, Maria Carolina; Schmidt, Amand Floriaan; Jefferis, Barbara; Wannamethee, S. Goya; Lawlor, Debbie A.; Kivimaki, Mika; Kumari, Meena; Gaunt, Tom R.; Ben‐Shlomo, Yoav; Tillin, Therese; Menon, Usha; Providencia, Rui; et al.
Abstract : Background: We aimed at investigating the association of circulating fatty acids with coronary heart disease (CHD) and stroke risk. Methods and Results: We conducted an individual‐participant data meta‐analysis of 5 UK‐based cohorts and 1 matched case‐control study. Fatty acids (ie, omega‐3 docosahexaenoic acid, omega‐6 linoleic acid, monounsaturated and saturated fatty acids) were measured at baseline using an automated high‐throughput serum nuclear magnetic resonance metabolomics platform. Data from 3022 incident CHD cases (13 104 controls) and 1606 incident stroke cases (13 369 controls) were included. Logistic regression was used to model the relation between fatty acids and odds of CHD and stroke, adjusting for demographic and lifestyle variables only (ie, minimally adjusted model) or with further adjustment for other fatty acids (ie, fully adjusted model). Although circulating docosahexaenoic acid, but not linoleic acid, was related to lower CHD risk in the fully adjusted model (odds ratio, 0.85; 95% CI, 0.76–0.95 per standard unit of docosahexaenoic acid), there was evidence of high between‐study heterogeneity and effect modification by study design. Stroke risk was consistently lower with increasing circulating linoleic acid (odds ratio for fully adjusted model, 0.82; 95% CI, 0.75–0.90). Circulating monounsaturated fatty acids were associated with higher CHD risk across all models and with stroke risk in the fully adjusted model (odds ratio, 1.22; 95% CI, 1.03–1.44). Saturated fatty acids were not related to increased CHD risk in the fully adjusted model (odds ratio, 0.94; 95% CI, 0.82–1.09), or stroke risk. Conclusions: We found consistent evidence that linoleic acid was associated with decreased risk of stroke and that monounsaturated fatty acids were associated with increased risk of CHD. The different pattern between CHD and stroke in terms of fatty acids risk profile suggests future studies should be cautious about using composite events. Different study designs are needed to assess which, if any, of the associations observed is causal.